Rhythmic Gesture in Mozart: Le nozze di Figaro & Don Giovanni - Allanbrook, Wye Jamison 1943-2010 (Chicago, IL London University of Chicago Press, 1986)
Wye Jamison Allanbrooks widely influential Rhythmic Gesture in Mozart challenges the view that Wolfgang Amadeus Mozart's music was a pure play of key and theme, more abstract than that of his predecessors. Allanbrook's innovative work shows that Mozart used a vocabulary of symbolic gestures and musical rhythms to reveal the nature of his characters and their interrelations. The dance rhythms and meters that pervade his operas conveyed very specific meanings to the audiences of the day.
Originally published in 1983
Keywords: Mozart, Wolfgang Amadeus -- 1756-1791; 18th Century (1701-1800); Musical analysis; Rhythm; Topos; Opera buffa; Dance; Vienna (Austria)